The study of clinical and laboratory parameters of elderly patients with arterial hypertension and post-covid syndrome. (Bangladesh Journal of Medical Science, 2025)
Since the onset of the COVID-19 pandemic, the coronavirus infection (COVID-19) has evolved into a serious global issue, widely discussed and studied by scientists around the world. The complexity of researching and classifying this disease lies in the absence of unified criteria: symptoms vary greatly, diagnostic thresholds fluctuate within wide ranges, and the clinical picture is complex and diverse. It largely depends not only on the patient’s age but also on their prior pathological history, quality of life, and geographical location. Under these circumstances, special attention must be paid to the study of diseases that have become increasingly prevalent, are associated with a high frequency and variety of complications, and have acquired new clinical features following COVID-19. In the course of our study, we systematized the main symptoms most characteristic of patients with cardiovascular pathology and post-COVID syndrome (PCS), comprising the main group (51 patients). The control group consisted of patients with similar cardiovascular conditions but without PCS (94 patients), assessed by clinical and laboratory parameters. In the main group, changes in blood laboratory values were observed, with the most prominent being elevated levels of blood enzymes—LDH, CPK, AST, and ALT. Among these, CPK and LDH were the most significant, which elevated levels indicating prolonged tropism of the virus toward vascular endothelium. The levels of SARS-CoV-2-specific IgG antibodies in both groups reflected the degree of immunological response and overall immune status.BJMS, Vol. 24 No. 03 July’25 Page : 975-983